2013
DOI: 10.1096/fj.13-245621
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin‐1 gene deletion reduces breast tumor growth and lung metastasis in tumor‐producing MMTV‐PyVT mice

Abstract: Aquaporin 1 (AQP1) is a plasma membrane water-transporting protein expressed strongly in tumor microvascular endothelia. We previously reported impaired angiogenesis in implanted tumors in AQP1-deficient mice and reduced migration of AQP1-deficient endothelial cells in vitro. Here, we investigated the consequences of AQP1 deficiency in mice that spontaneously develop well-differentiated, luminal-type breast adenomas with lung metastases [mouse mammary tumor virus-driven polyoma virus middle T oncogene (MMTV-Py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 39 publications
3
65
0
Order By: Relevance
“…The vessel density was reduced with abnormal microvascular structure in tumors, and the lung metastasis was greatly inhibited in AQP1 −/− MMTV-PyVT mouse model [32]. Meanwhile, the AQP1 mRNA and protein levels in mouse heart were significantly reduced by ischemia, hypoxia, and cardioplegia [25].…”
Section: Discussionmentioning
confidence: 98%
“…The vessel density was reduced with abnormal microvascular structure in tumors, and the lung metastasis was greatly inhibited in AQP1 −/− MMTV-PyVT mouse model [32]. Meanwhile, the AQP1 mRNA and protein levels in mouse heart were significantly reduced by ischemia, hypoxia, and cardioplegia [25].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it is confirmed that aquaporin 1 plays an active role in carcinogenesis, with an involvement in cell migration, proliferation, and angiogenesis [56][57][58][59]. Collectively, the facts mentioned above may account for much interest in identification of aquaporin 1 as a potential marker for MPM.…”
Section: Aquaporin 1 (Aqp1)mentioning
confidence: 89%
“…AQP1-expressing tumor cells have enhanced metastatic potential and increased local infiltration compared with those lacking AQP1 [6,19,20] . Knockdown of AQP1 in osteosarcoma cells can inhibit cell proliferation and significantly arrest cell cycle G1.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies have focused on the regulation of AQP1 expression in tumor cells and its role in pathogenesis, growth, metastatic potential and tumor progression [2,20] .…”
Section: Discussionmentioning
confidence: 99%